2017
DOI: 10.7226/jtfm.23.1.16
|View full text |Cite
|
Sign up to set email alerts
|

The Refusal of Livestock Owners Towards Exclusion Policy In Protected Area

Abstract: Development of protected forest is often considered to be a way to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
2
0
2
Order By: Relevance
“…Many researchers conducted various studies on forest protected (e.g. Purnomo 2003;Ginoga et al 2005;Nandini 2013;Hidayat 2014;Kurniadi et al 2017;Dako et al 2018) and these studies showed that forest protected faces many problems due to the increasing social difficulty of people living around the forest which is usually due to population growth, deforestation and land degradation, and reduced public access to natural resources (Simon 2003). Traditionally, the needs of community around the forest are fulfilled through natural resource management based on traditional knowledge, local wisdom, and ecological beliefs (Berkes 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers conducted various studies on forest protected (e.g. Purnomo 2003;Ginoga et al 2005;Nandini 2013;Hidayat 2014;Kurniadi et al 2017;Dako et al 2018) and these studies showed that forest protected faces many problems due to the increasing social difficulty of people living around the forest which is usually due to population growth, deforestation and land degradation, and reduced public access to natural resources (Simon 2003). Traditionally, the needs of community around the forest are fulfilled through natural resource management based on traditional knowledge, local wisdom, and ecological beliefs (Berkes 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Anak perempuan yangdibawalaritanpa mas kawin, perselingkuhan dan pemerkosaan dapat memicu perang suku. Menurut (Kurniadi et al, 2017) kesamaan terhadap nilai wanita menjadi tolak ukur untuk timbulnya konflik di dua daerah yang berbeda budaya disebut sebagai tradisi yang alamiah.…”
Section: Hasil Dan Pembahasanunclassified
“…Dengan demikian masyarakat dengan sadar menjaga dan melindungi serta berpartisipasi jika pemerintah mengadakan GNRHL/reboisasi. Menurut Kurniadi et al (2017), pengembangan hutan lindung dianggap sebagai cara untuk melestarikan keanekaragaman hayati dan jasa ekosistem. Demikian juga menurut sebagian responden menginginkan tetap sebagai HLM karena untuk penetapan hutan lindung membutuhkan biaya sangat mahal mulai dari penunjukan sampai penetapan.…”
Section: Persepsi Masyarakatunclassified